2014
DOI: 10.9734/ajea/2015/13398
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Cytokinin Promotes Epipremnum aureum L. Growth through Enhanced Dry Weight Assimilation rather than through Changes in Partitioning

Abstract: Aims: Benzylaminopurine (BAP) sprays have been shown to increase leaf size and leaf appearance rate, as well as biomass accumulation in pot-grown Epipremnum aureum L. BAP-mediated enhanced growth could either be the consequence of a higher investment of dry weight in leaf area development thus leading to a positive dry weight accumulation feedback, to a promoting effect on dry weight assimilation per unit leaf area. Study Design: A randomized complete block factorial design with three blocks was used. Original… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…These last results indicated higher frond thickness and a proportional higher photo assimilate partition to leaves as pot volume increased. The strong correlation between most growth parameters related to frond area expansion and frond anatomical structure and RGR were similar to those found for other ornamental vascular plants [15,16,17,18].…”
Section: Relationships Between Rla (A) Rlae (B) Rgr (C) Nar (D)supporting
confidence: 81%
“…These last results indicated higher frond thickness and a proportional higher photo assimilate partition to leaves as pot volume increased. The strong correlation between most growth parameters related to frond area expansion and frond anatomical structure and RGR were similar to those found for other ornamental vascular plants [15,16,17,18].…”
Section: Relationships Between Rla (A) Rlae (B) Rgr (C) Nar (D)supporting
confidence: 81%
“…Because the environmental conditions (daily temperatures and photon flux radiation) in the three experiments were quite different, we can hypothesize that endogenous cytokinin synthesis can change in response to environmental variables such as temperature and photon flux radiation. In agreement with this assumption, several studies have found a positive interaction between cytokinins and photosynthetic active radiation [9,10,29] or temperature [30,31]. We may also speculate that some of the dopamine-inhibited physiological processes had different endogenous cytokinin thresholds, which define the final response of plants.…”
Section: Bapsupporting
confidence: 76%
“…To understand these results, it must be kept in mind that the primary shoot apical meristem is responsible for generating all above ground organs and is controlled by hormones, which regulate biosynthesis and transport of other hormones, and by hormone interactions. These hormones include auxins, cytokinins and gibberellins, which act both independently and in combination to regulate meristem function [9,10,14,18]. Leaves are formed into an initial group of cells within the meristem; one of the earliest markers for leaf initiation is the downregulation of the KNOTTED and WUSCHEL genes in these cells [19].…”
Section: Bapmentioning
confidence: 99%
See 1 more Smart Citation
“…The favorable effect of GA 3 on the plant growth may be attributed to its effect on stimulating the expression of enzymes involved in cell wall loosening and genes controlling cell division and also stimulating microtubule rearrangements associated with cell expansion (Satish and Manju, 2018). It was stated that the increase of plant growth by BA mainly associated with higher net assimilation rates and increased N content per unit leaf area (Di Benedetto and Galmarini, 2015), while increasing plant growth due to GA 3 may be attributed to its influence on increasing photosynthesis rate through increasing leaf surface (Lima et al, 2014). Moreover, increasing plant growth as a result of combined growth hormones with nutrient may be owing to physiological role of hormones and nutrient in synthesis of the plant phytochemicals through the action of various enzymes activity and protein synthesis (Tandel et al, 2018).…”
Section: Effect Of Npk With Plant Growth Regulators Treatmentsmentioning
confidence: 99%